Tnfaip3 expression in pulmonary conventional type 1 Langerin‐expressing dendritic cells regulates T helper 2‐mediated airway inflammation in mice. Issue 10 (14th June 2020) - Vroman, Heleen; van Uden, Denise; Bergen, Ingrid M.; van Hulst, Jennifer A. C.; Lukkes, Melanie; van Loo, Geert; Clausen, Björn E.; Boon, Louis; Lambrecht, Bart N.; Hammad, Hamida; Hendriks, Rudi W.; Kool, Mirjam
Abstract: Background: Conventional type 1 dendritic cells (cDC1s) control anti‐viral and anti‐tumor immunity by inducing antigen‐specific cytotoxic CD8 + T‐cell responses. Controversy exists whether cDC1s also control CD4 + T helper 2 (Th2) cell responses, since suppressive and activating roles have been reported. DC activation status, controlled by the transcription factor NF‐κB, might determine the precise outcome of Th‐cell differentiation upon encounter with cDC1s. To investigate the role of activated cDC1s in Th2‐driven immune responses, pulmonary cDC1s were activated by targeted deletion of A20/ Tnfaip3, a negative regulator of NF‐κB signaling. Methods: To target pulmonary cDC1s, Cd207 (Langerin)‐mediated excision of A20/ Tnfaip3 was used, generating Tnfaip3 fl/fl x Cd207 +/cre ( Tnfaip3 Lg‐KO ) mice. Mice were exposed to house dust mite (HDM) to provoke Th2‐mediated immune responses. Results: Mice harboring Tnfaip3 ‐deficient cDC1s did not develop Th2‐driven eosinophilic airway inflammation upon HDM exposure, but rather showed elevated numbers of IFNγ‐expressing CD8 + T cells. In addition, Tnfaip3 Lg‐KO mice harbored increased numbers of IL‐12–expressing cDC1s and elevated PD‐L1 expression in all pulmonary DC subsets. Blocking either IL‐12 or IFNγ in Tnfaip3 Lg‐KO mice restored Th2 responses, whereas administration of recombinant IFNγ during HDM sensitization in C57Bl/6 mice blocked Th2 development. Conclusions: These findings indicate that the activation status of cDC1s, shown by their specific expression of co‐inhibitory molecules and cytokines, critically contributes to the development of Th2 cell–mediated disorders, most likely by influencing IFNγ production in CD8 + T cells. Abstract : Mice harboring Tnfaip3 ‐deficient cDC1s ( Tnfaip3 Lg‐KO mice) do not develop Th2‐driven eosinophilic airway inflammation upon house dust mite exposure but have elevated numbers of pulmonary IFNγ‐expressing CD8 + T‐cells. In the lungs of Tnfaip3 Lg‐KO mice, cDC1s have increased IL‐12 and PD‐L1 expression. Both IL‐12 and IFNγ are involved in the reduced Th2‐response observed in Tnfaip3 Lg‐KO mice. Abbreviations: cDC, conventional dendritic cell; PD‐L1, programmed death ligand 1; Tnfaip3, TNF alpha‐induced protein 3.